Is tactical combat casualty care in terrorist attacks suitable for civilian first responders?. Issue 4 (October 2021) - Borgers, Felix; Van Boxstael, Sam; Sabbe, Marc
Abstract : INTRODUCTION: Prehospital management of intentional mass casualty incidents is a unique challenge to Emergency Medical Services. Tactical Combat Casualty Care (TCCC) and the use of tourniquets for extremity hemorrhage have already proven to reduce mortality on the battlefield. This literature review aims to determine the place of these military concepts in a civilian high-threat prehospital setting. METHODS: The PubMed database was searched for articles published between January 1, 2000, and December 1, 2019, containing descriptions, discussions, or experiences of the application of tourniquets or other TCCC-based interventions in the civilian prehospital setting. Data extraction focused on identifying important common themes in the articles. RESULTS: Of the 286 identified articles, 30 were selected for inclusion. According to the Oxford Centre for Evidence-based Medicine Levels of Evidence, overall level of evidence was low. Most articles were observational, retrospective cohort studies without a nontourniquet control group. Outcome measures and variables were variably reported. Two articles specifically analyzed tourniquet use during high-threat situations, and three described their application by law enforcement personnel. Overall, tourniquets were found to be effective in stopping major limb bleeding. Reported mortality was low and related complications appeared to be infrequent. Only four articles mentioned the application of other TCCC-based maneuvers, such as airway and respiratory management. CONCLUSION: This literature review shows that tourniquets appear to be safe tools associated with few complications and might be effective in controlling major bleeding in civilian limb trauma. For example, during mass casualty incidents, their use could be justified. Training and equipping ambulance and police services to deal with massive bleeding could likewise improve interoperability and victim survival in a civilian high-threat prehospital setting. More qualitative research is needed to further evaluate the effects of hemorrhage control training for first responders on patient outcomes. Literature describing the application of other TCCC-based principles is limited, which makes it difficult to draw conclusions regarding their use in a civilian setting. LEVEL OF EVIDENCE: Systematic review, level III.